2021 Guideline for Management of Patients With Lower-Extremity Wounds Due to Diabetes Mellitus and/or Neuropathic Disease: An Executive Summary. Issue 3 (May 2022) - Bonham, Phyllis A.; Brunette, Glenda; Crestodina, Lea; Droste, Linda R.; González, Arturo; Kelechi, Teresa J.; Ratliff, Catherine R.; Varnado, Myra F.
Abstract : This article provides an executive summary of the Wound, Ostomy, and Continence Nurses Society's (WOCN) "2021 Guideline for Management of Patients With Lower-Extremity wounds Due to Diabetes Mellitus and/or Neuropathic Disease." This executive summary presents an overview of the systematic process used to update and develop the guideline and recommendations from the guideline for screening and diagnosis, assessment, and management and education of patients with lower-extremity wounds due to diabetes mellitus and/or neuropathic disease. In addition, the executive summary provides suggestions for implementing recommendations from the guideline. The guideline is a resource for WOC nurse specialists and other nurses and health care professionals who work with adults who have/or are at risk for lower-extremity wounds due to diabetes mellitus/neuropathic disease. The complete guideline includes the evidence and references supporting the recommendations, and it is available in print and electronically from the Wound, Ostomy, and Continence Nurses Society, 1120 Rt 73, Suite 200, Mount Laurel, New Jersey, 08054; Web site: www.wocn.org .